A Study of Management on Selected Heritage Tourism of South India with Special Reference to Thanjavur: Enhancing Return to Expectation of Local Tourists in South Indian Heritage Tourism (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Heritage tourism includes administrations to tourists with the event to comprehend, and delight from uniqueness of regular and heritage highlights. Cultural legacy, condition, openness and offices are significant highlights of heritage tourism places. Huge contrast is winning among socioeconomics of local tourists and highlights of heritage tourism places. Cultural legacy, traditional values, nature and condition and offices have huge sway on return to expectation of residential tourists. So as to improve return to expectation of local tourists, heritage tourism spots ought to orchestrate cultural projects and they should give traditional neighborliness. Furthermore, spots ought to keep up well and they should have recreational exercises.